Population Control of Viruses Insect Vectors in Chili with Plastic Mulch - Yuliadhi, K.A.; Phabiola, T.A.; Siadi, K. (Advances in Tropical Biodiversity and Environmental Sciences, 2017)
The incidence of diseases caused by pathogenic viruses in chili is still a major problem in reducing the production of chili in Indonesia. Most agricultural crops are hosts for one or more types of plant viruses, so the viru s continued to be a problem in the tropics. Virus is passive, requires intermediaries vector to be transmitted to other plants. The goal of this research was to develop control strategies for aphids that act as a viral vector and pest chili plants using plastic mulch. Control design that was developed in this study based on the habits of local farmers, using plastic mulch with two colors, black and silver. Mulching is done to dispel the arrival aphids into the chili crop, at the same time preventing the emergence of weeds that act as alternative hosts of the virus. The use of silver plastic mulch to control vector viral populations was better compared to black plastic mulch during  chili planting. The use of silver plastic mulch can improve yields of chili crops. K eywords : Aphid, whiteflies, Chili chili, virus